EIB Working Papers 2019/05 - Skill shortages and skill mismatch in Europe A review of the literature (Volume 2019/5) - Brunello, Giorgio (European Investment Bank, 2019)
Labour markets are undergoing structural transformation due to globalisation, demographic trends, advancing digital technologies and automation and changes in labour market institutions. Against this background, businesses increasingly report that the limited availability of skills poses an impediment to corporate investment. Genuine skill constraints can negatively affect labour productivity and hamper the ability to innovate and adopt technological developments. For individual Europeans, not having "the right skills" limits employability prospects and access to quality jobs. For Europe at large, persistent skill gaps and mismatches come at economic and social costs.This paper reviews the recent economic literature on skill mismatch and skill shortages, with a focus on Europe. It questions:how the job requirements of individuals can be measured;whether skill shortages stated by employers reflect the lack of suitable candidates or are due instead to the wage and working conditions being offered;what economic costs are posed by skill mismatch and shortages; andhow policy can address the issue of skills, including the role of EU policies.